"Joe Biden is a corrupt politician!": Impoliteness in Donald Trump’s Tweets - Fithrotul Izzah; Thomas Joko Priyo Sembodo (Lexicon, 2022)
This study aims at investigating impoliteness strategies in 351 tweets taken from Donald Trump’s personal Twitter account (@realDonaldTrump) from the first presidential debate to the Election Day of the 2020 United States presidential election. The current study employed Bousfield’s (2008) taxonomy of impoliteness strategies to analyze the data. There are 368 occurrences of eleven impoliteness strategies across 351 tweets. The most common impoliteness strategy is use inappropriate identity markers (23.59%), followed by threaten/frighten (21.13%) and condescend, scorn, and ridicule (20.59%). These strategies were employed to attack and discredit Trump’s political opponents as well as attracting prospective voters. On the other hand, two impoliteness strategies, namely hinder/block and enforce role shift, were not identified in the tweets. The results indicate that Donald Trump’s tweets exhibited impoliteness and that it played quite a significant role as a means of political campaign during the 2020 United States Presidential Election.